2008
DOI: 10.1038/sj.bjc.6604087
|View full text |Cite
|
Sign up to set email alerts
|

Profiling influences of senescent and aged fibroblasts on prostate carcinogenesis

Abstract: Experimental evidence suggests that ageing-associated alterations in the tissue microenvironment act to promote prostate carcinogenesis. In this review, we survey the cellular state of senescence, review its causes, and describe associations with ageing and cancer. We further discuss senescent stromal gene expression changes, which may mediate these effects, and that may serve as therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 28 publications
1
28
0
4
Order By: Relevance
“…We now report that PCa-AFs and MFs secrete a low level of IL-6 and a large amount of MMPs, which are responsible for inducing a clear EMT in PC3 cells. In keeping with our findings, production of MMP-2 and MMP-9, as well as IL-6 levels, have been associated with fibroblast senescence, a phenotype of stromal fibroblasts involved in prostate carcinogenesis and tumor progression (32,33).…”
Section: Discussionsupporting
confidence: 69%
“…We now report that PCa-AFs and MFs secrete a low level of IL-6 and a large amount of MMPs, which are responsible for inducing a clear EMT in PC3 cells. In keeping with our findings, production of MMP-2 and MMP-9, as well as IL-6 levels, have been associated with fibroblast senescence, a phenotype of stromal fibroblasts involved in prostate carcinogenesis and tumor progression (32,33).…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, it has been shown that many genes overexpressed in senescent fibroblasts are also upregulated in CAFs (47). Moreover, LOXL2 belongs to a gene expression signature in fibroblasts that is upregulated in response to serum and has the ability to predict cancer progression (48) and outcome in patients with breast cancer (49).…”
Section: Discussionmentioning
confidence: 99%
“…dans l'organisme [38] (Figure 3). De fait, plusieurs études ont montré que les cellules sénescentes s'accumulent effectivement dans les compartiments stromaux des individus âgés où elles altèrent profondément les caractéristiques de croissance des cellules épithéliales prénéopla-siques [39]. La question est maintenant de savoir comment séparer les « bons » et les « mauvais » aspects de la sénescence dans une tumeur donnée.…”
Section: Une Nouvelle « Pléiotropie Antagoniste »unclassified